Dynamics of Soil Organic Carbon at Different Elevations in Cocoa Land-Use Systems - Danang Widjajanto; Rachmat Zainuddin; Rois; Abdul Rahman; Moh. Adnan Khaliq; Uswah Hasanah; Rosmaniar Gailea; Fera (Jurnal Penelitian Pendidikan IPA, 2025)
Soil organic carbon (SOC) is essential for sustaining soil quality, especially in sloped agricultural landscapes prone to erosion and degradation. This study aimed to analyze SOC dynamics across different elevations (400, 600, and 800 meters above sea level) in cocoa-based land-use systems and examine its relationships with some key physical properties. Soil sampling was conducted using a stratified random design, and laboratory analyses were carried out using standard methods. The results showed that SOC increased with elevation due to cooler temperatures, slower organic matter decomposition, and higher surface litter accumulation. Polynomial regression revealed non-linear relationships between SOC and soil properties, with significant coefficients of determination: SOC vs. bulk density (R² = 0.82), SOC vs. penetration resistance (R² = 0.44), and SOC vs. saturated hydraulic conductivity (R² = 0.37). Moderate SOC levels (around 2.3% – 3.0%) were associated with improved soil structure, lower bulk density, higher hydraulic conductivity, and reduced penetration resistance. However, excessive organic inputs beyond the optimum may reduce these benefits due to incomplete decomposition. A similar curvilinear pattern was found between surface litter and SOC content. These findings highlight the importance of optimizing organic matter management in cocoa systems on sloped lands to enhance soil physical conditions and promote sustainable agriculture.